Ius patronatus as viewed by Edward Rittner - Robert Kantor (The Person and the Challenges. The Journal of Theology, Education, Canon Law and Social Studies Inspired by Pope John Paul II, 2021)
Patronage can be defined as a group of privileges and duties granted by ecclesiastical authorities to the faithful who founded a church, chapel or benefice and to those who acquired this right from them. This is how Prof. Edward Rittner, the Rector of the University of Lviv, understood this concept. This article, entitled “Ius patronatus as viewed by Edward Rittner”, presents the notion of patronage itself, as well as related issues, such as: the ways of patronage acquisition, the possibilities of patronage transfer, the content of ius patroantus and finally the ways of patronage expiration. This article is based on Prof. Rittner’s lecture contained in his textbook “Prawo kościelne katolickie” (in English: Catholic Ecclesiastical Law), volume I, fourth edition from Lviv dated 1912.